DESTINASI PARIWISATA HALAL DI KOTA BANDUNG - Syits Qory; Syifa Ulya; Wina Royani; Yuliawanti Dewi (LIKUID: Jurnal Ekonomi Industri Halal, 2021)
Today, halal tourism is very popular and attractive to several regions in Indonesia, including the province of West Java. Halal tourism is supported by its majority Muslim population and has a positive impact on the economic development of the community. This study aims to review the strengths, weaknesses, opportunities and threats of halal tourism in Bandung, through SWOT analysis method. The results showed, the strong encouragement of the local government, the availability of many tourist destinations and religious facilities, as well as the close orientation of the Bandung community with Islam became the basis of its strength. The disadvantage is that service providers are still not optimal for tourists. While the opportunity is access to tourist attractions that make it easier for tourists to visit. Then the threat is other regions in Indonesia that are equally developing halal tourism. By compiling and implementing a strategy based on the results of the analysis, it is hoped that Bandung will be better in developing its Halal Tourism in order to advance economic conditions, and become the best halal tourist destination in the province of West Java.Keywords: Halal tourism, SWOT Analysis, Farm House Bandung, empowerment